2020
DOI: 10.1088/1755-1315/564/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bacteria from mangrove forest in Mamburungan, Tarakan City

Abstract: Bacteria has a main role in the food chain and waters productivity. Bacteria in the mangrove ecosystem mostly are from litter, sediment, and sea waters. The research objective is to determine the genus of bacteria that was found in Avicennia marina and Sonneratia alba leaf litter as well as bacteria in waters and sediment from a mangrove forest in Mamburungan. The method was designed by using explorative descriptive, and the analysis parameter was the genus. This study was done in the field experimentally with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…This trend also extends to other bacteria inhabiting mangrove soil, which can thrive within pH levels from 5 to 7 and under a maximum temperature of 40℃ (Behera et al 2016). It has been observed that the genera Rhizophora, Sonneratia, and Avicennia are the plant species where Vibrio bacteria are most commonly found (Yahya et al 2014;Yulma et al 2017Yulma et al , 2020. The result of this study aligns with these findings, as Vibrio was most abundant in S. alba.…”
Section: Physico-chemical Parameterssupporting
confidence: 87%
See 1 more Smart Citation
“…This trend also extends to other bacteria inhabiting mangrove soil, which can thrive within pH levels from 5 to 7 and under a maximum temperature of 40℃ (Behera et al 2016). It has been observed that the genera Rhizophora, Sonneratia, and Avicennia are the plant species where Vibrio bacteria are most commonly found (Yahya et al 2014;Yulma et al 2017Yulma et al , 2020. The result of this study aligns with these findings, as Vibrio was most abundant in S. alba.…”
Section: Physico-chemical Parameterssupporting
confidence: 87%
“…Certain microorganisms, like nitrogen-fixing, phosphate-solubilizing, and sulfatereducing bacteria, isolated from mangrove soil, positively impact mangrove growth (Sukmawati et al 2022). In return, mangroves provide a habitat for these microbes to thrive and provide essential nutrients to support their growth (Yulma et al 2020). This interplay highlights the importance of microorganisms in mangrove forests for boosting productivity, conservation, and ecosystem restoration (Erazo and Bowman 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These findings brought attention to the microbial composition of the Sundarbans mangrove forest. The previous study reported that the 16S rRNA genes were used to determine the microbial community in the Bangladeshi Sundarbans [103] , and provided insights into the functional and phylogenetic diversity of microbes along the Bay of Bengal Coastline in Bangladesh [ 90 , 102 ] have explored and characterized a total of twenty-five bacteria in the mangrove ecosystem, primarily from litter, sediment, and sea waters, and the dominant bacteria found in these environments were Bacillus .…”
Section: Discussionmentioning
confidence: 99%
“…The indirect benefits of mangroves for fisheries as a food supply for marine communities through the detritus food chain which starts from all mangrove leaf litter. The decomposition of organic matter, also called the mineralization process, is a microbial process (decomposer) in obtaining energy for its propagation [5].…”
Section: Introductionmentioning
confidence: 99%